2016
DOI: 10.1016/j.ajic.2015.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of intravenous colistin use for the treatment of nosocomial multidrug-resistant Acinetobacter baumannii infections in a pediatric intensive care unit

Abstract: Intensive care unit environmental surfaces are contaminated by multidrugresistant bacteria in biofilms: combined results of conventional culture, pyrosequencing, scanning electron microscopy, and confocal laser microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…The major side effects of treatment with colistin tend to be neurotoxicity and nephrotoxicity. Previous studies have observed nephrotoxicity at a rate of 0% and 12.5% (17,(27)(28)(29)(30). Seven (8.5%) patients in our study developed nephrotoxicity.…”
Section: Discussionsupporting
confidence: 55%
“…The major side effects of treatment with colistin tend to be neurotoxicity and nephrotoxicity. Previous studies have observed nephrotoxicity at a rate of 0% and 12.5% (17,(27)(28)(29)(30). Seven (8.5%) patients in our study developed nephrotoxicity.…”
Section: Discussionsupporting
confidence: 55%
“…With AKI n (%) The AKI rates reported among pediatric studies evaluating colistin efficacy and safety ranged from 0 to 22.8% (Falagas et al, 2009a;_ Işgüder et al, 2016;Kapoor et al, 2013;Karbuz et al, 2014;Karli et al, 2013;Paksu et al, 2012;Sahbudak Bal et al, 2018;Tamma et al, 2013), while the rate was found to be as high as 51% in an adult study (Miano et al, 2018). Among pediatric studies, the differing AKI rates were probably caused by many factors, such as patient characteristics, number of patients studied, AKI definition, and colistin dosing.…”
Section: Totalmentioning
confidence: 99%
“…In adults, the acute kidney injury (AKI) rate was reported as 51% in patients using colistin, while in the matched controls the AKI rate was 22% (Miano et al, 2018). In children, the nephrotoxicity rate has been reported over a range from 0 to 22.8%, based on various nephrotoxicity definitions (Falagas et al, 2009a;_ Işgüder et al, 2016;Kapoor et al, 2013;Karbuz et al, 2014;Karli et al, 2013;Paksu et al, 2012;Sahbudak Bal et al, 2018;Tamma et al, 2013). The nephrotoxicity usually occurred when colistin was given concomitantly with other, more nephrotoxic drugs, such as vancomycin or aminoglycosides (Rattanaumpawan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…colistinus [ 14 ], is a potent broad-spectrum antimicrobial. This antibiotic is commonly used for the treatment of challenging Gram-negative pathogens[ 15 ], including A . baumannii .…”
Section: Introductionmentioning
confidence: 99%